Analisis Desentralisasi Fiskal, Pembangunan Manusia, dan Pertumbuhan Ekonomi Regional di Indonesia - Satria Ali Hussain; Ali Anis (Universitas Negeri Padang, 2024)
This study aims to identify and analyze the effect of fiscal decentralization and human development on economic growth in Indonesia. This research is descriptive and associative with a quantitative approach. The data used is secondary data analyzed using panel data regression, with the Fixed Effect Model (FEM) method, covering time series from 2014 to 2022 and cross section of 34 provinces in Indonesia sourced from the Ministry of Finance and BPS. The results showed that fiscal decentralization has a positive and significant influence on economic growth in Indonesia. In contrast, human development has a negative and significant effect on economic growth in Indonesia.